VALUE OF MORALITY IN MUSIC OF CONFUCIUS (551-479 BC) (Harmonia: Journal of Arts Research and Education, 2013)
In line with the basic concept of ”jen” and some things related to the virtue, Confucius emphasized on the maintenance of beauty and music. The emphasis of those two things illustrated the feeling of self-dualism that is morals and aesthetics. Talking about the development of one’s personality, Confucius said, ”Through the poetry one’s attention will grow, through the various rites one’s mentality will be set; through music one becomes perfect (Analects of Confucius, chapter 8, section 8). The maintenances of beauty and music were expected to be part of one’s sublime nature and human civilization, according to Confucius, maintenance and reasonable combination between the yen and the beauty was indeed necessary for the self perfection and the improvement from disgraceful deeds. Just like a house with a strong base had certainly a proportional shape; then, one with his opportunities to do well was supposed to be able to express it with deep thoughts (feelings) and with good manners. Sejalan dengan konsep dasar dari “jen” dan beberapa hal yang berkaitan dengan kebaikan, Konfusius lebih menekankan pada pemeliharaan keindahan dan musik. Dua hal penekanan itu menggambarkan perasaan dualisme akan diri pribadi yaitu moral dan estetika. Membicarakan tentang perkembangan kepribadian seseorang, Konfusius berkata, “lewat puisi perhatian seseorang akan tumbuh, lewat berbagai upacara tabiat seseorang diatur; lewat musik seseorang menjadi  sempurna (Ana¬lects of Konfusius, bab 8, seksi 8). Pemeliharaan keindahan dan musik diharapkan mampu menjadi bagian dari sifat luhur seseorang dan peradaban masyarakat menurut Konfusius, pemeliharaan dan kombinasi yang wajar antara yen dan keindahan memang perlu untuk kesempurnaan diri dan perbaikan dari sifat-sifat tercela. Seperti halnya sebuah rumah dengan pondasi (dasar) yang kuat tentu memiliki bentuk yang menyenangkan  maka seharusnya orang dengan kesempatan yang dimilikinya untuk berbuat baik mampu mengungkapkannya dengan pikiran yang mendalam (perasaan) dan dengan cara-cara yang baik).